The Law of Nations and Natural Law 1625-1800 - Zurbuchen, Simone (Early Modern Natural Law: Studies & Sources, 2019)
Twelve international scholars offer innovative studies of the law of nations from the Peace of Westphalia to the Enlightenment. The focus is on little known contexts and sources, and on novel interpretations of classics in the field. Readership: Philosophers, historians, legal scholars and political theorists interested in the history of international law, and anyone concerned with modern natural law and Emer de Vattel's Law of Nations.